2010
DOI: 10.1152/jn.00122.2010
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Conductivity Profile in the Somatosensory Barrel Cortex of Wistar Rats

Abstract: Microelectrode arrays used to record local field potentials from the brain are being built with increasingly more spatial resolution, ranging from the initially developed laminar arrays to those with planar and three-dimensional (3D) formats. In parallel with such development in recording techniques, current source density (CSD) analyses have recently been expanded up to the continuous-3D form. Unfortunately, the effect of the conductivity profile on the CSD analysis performed with contemporary microelectrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 59 publications
6
99
0
Order By: Relevance
“…It has been shown that, as a consequence of two major dielectric relaxation mechanisms (i.e., the counterion and interfacial polarizations), the brain tissues are highly dispersive for the frequency range of the electrophysiological recordings (Gabriel et al 1996(Gabriel et al , 2009). In addition, the conductivity and permittivity depend on the location (i.e., inhomogeneity) and direction (i.e., anisotropy) inside the brain (Gabriel et al 2009;Goto et al 2010). Therefore, as charge moves, its effect on externally measured fields can depend on location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that, as a consequence of two major dielectric relaxation mechanisms (i.e., the counterion and interfacial polarizations), the brain tissues are highly dispersive for the frequency range of the electrophysiological recordings (Gabriel et al 1996(Gabriel et al , 2009). In addition, the conductivity and permittivity depend on the location (i.e., inhomogeneity) and direction (i.e., anisotropy) inside the brain (Gabriel et al 2009;Goto et al 2010). Therefore, as charge moves, its effect on externally measured fields can depend on location.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters used in the vCSD method were 1) the intergrid distance ⌬, which was 50 m, and 2) the radial/tangential conductivities and radii for all cortical layers, which were previously estimated by Goto et al (2010) for the somatosensory cortex of adult Wistar rats. We applied the average reference operator (Pascual-Marqui 1999) to the Green's function matrices, event-related LFPs, and SRPs to remove undesirable signals from the reference electrode (Bertrand et al 1985).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that this question has remained unresolved, with a number of studies reporting an anisotropic and homogeneous σ (Nicholson and Freeman 1975;Logothetis et al 2007) (Fig. 3d, e) to strongly anisotropic and inhomogeneous (Goto et al 2010;Hoeltzell and Dykes 1979;Ranck 1973) and, finally, even of capacitive nature (Bédard and Destexhe 2009;Bédard et al 2004;Gabriel et al 1996).…”
Section: Biophysics Related To Electric Measurementsmentioning
confidence: 99%
“…Yet, others found the extracellular medium to be strongly anisotropic and inhomogeneous (Hoeltzell and Dykes 1979;Ranck 1973) or even of capacitive nature (Gabriel et al 1996;Bédard et al 2004;Bédard and Destexhe 2009). In a more recent study, Goto et al (2010) used extracellular recordings to measure the conductivity profile along the entire somatosensory barrel cortex in rodents using depth multi-electrode recordings and reported that radial and tangential conductivity values varied consistently across the six neocortical laminas. Thus, they showed that the electric properties of the extracellular medium in the living animal were anisotropic and inherently inhomogeneous, agreeing with the in vitro findings of Anastassiou et al (2015).…”
Section: Biophysics Related To Electric Measurementsmentioning
confidence: 99%